The Conflict Between Humanitarian Intervention and the Principle of Non-Intervention in Article 2(7) of the UN Charter - Daniel J. Hensley; Thomas P. Greer; Elena S. Fischer (Studies in Law and Justice, 2024)
This paper examines the conflict between the principle of non-intervention, enshrined in Article 2(7) of the United Nations Charter, and the practice of humanitarian intervention. The principle of non-intervention aims to protect state sovereignty by prohibiting external interference in domestic matters, but it faces challenges in the context of severe humanitarian crises. Through analysis of legal frameworks, ethical debates, and case studies such as Kosovo, Libya, and Syria, this paper explores the complexities of balancing respect for sovereignty with the moral imperative to protect human rights. The role of the UN Security Council in authorizing interventions and the influence of geopolitical dynamics are discussed, as well as the evolving doctrine of Responsibility to Protect (R2P). The paper concludes by highlighting the need for clearer international standards that reconcile non-intervention with the responsibility to prevent atrocities, offering insights into potential reforms for a more consistent approach to humanitarian intervention in international law.